Lactic acid bacteria mediated fermented soybean as a potent nutraceutical candidate - Sasithorn Sirilun (2018)
© 2017 Hainan Medical University Objective To study some soybean cultivars commonly used in Northern Thailand that exhibit high nutritional profile and to investigate the changes in bioactive principles and antioxidant capacity of the fermented soy broth that was prepared using the selected soybean cultivar and Lactobacillus paracasei HII02 mediated fermentation process. Methods The best soybean cultivar was subjected to fermentation, and then analyzed the phytochemical, antioxidant and nutritional changes by high performance liquid chromatography and spectrophotometric analysis. Results Sor Jor 2 soybean cultivar showed rich nutritional profile and was subjected to fermentation process. Lactobacillus paracasei HII02 mediated fermentation of Sor Jor 2 soybean exhibited stable physical and chemical characteristics. Lactic acid bacteria mediated fermentation also increased the aglycone forms of isoflavone content, exhibited antioxidant capacity and thereby enhanced the quality of the fermented soy broth. It also prevented the growth of coliforms in fermented soybean. Conclusions The study results suggest that fermented soybean is rich in nutrition and considered to be safe for consumption for the improvement of health and to treat the malnutrition.